(untitled) (Indian Journal of Animal Production and Management, 2014)
A total of 200 broiler chicks of Vencob-100 strain were procured and reared under standard management conditions till 42 days of experiment. After completion of one week they were divided into 8 groups according to different light regime mixing colour of light and intermittent light. The values for body weight (gm) at the end of 4th week of age under blue and green coloured light having light duration 20 L + 4D was differ significantly (P <0.05). The values for body weight gain (gm) at the end of 5th week of age under blue coloured light (20L + 4D) and green coloured light (18L + 6D) was differ significantly (P < 0.05). At the end of 6th week of age the feed conversion ratio of broiler chicken under blue light (18L + 6D) and under white light (23L + 1D) were differed significantly (P < 0.05). From the results it can be concluded that overall performance of blue coloured light and intermittent light show better performance on weekly mean body weight (gm) and weekly mean body weight gain than other coloured light and continuous light regime. When economic performance was taken into consideration it was seen that blue, green coloured light and intermittent light increase the profit.